PRESTIGE OR PREFERENCE? GENERATION Z’S PURCHASE DECISION BEHAVIOR TOWARD IPHONE AND SAMSUNG SMARTPHONES - Merliana, Ira; Putra, Febrianur Ibnu Fitroh Sukono; Kusuma, Pradana Jati; Oktoriza, Linda Ayu (Distribusi - Journal of Management and Business, 2026)
The development of digital technology has made smartphones a primary necessity for Generation Z, especially in the premium segment such as iPhone and Samsung. This study aims to analyze the influence of functional, emotional, social, and epistemic values on brand preference and purchase decisions, with brand preference as a mediating variable. The study employs a quantitative approach using an explanatory survey design involving 124 Generation Z students from the Faculty of Economics and Business at Dian Nuswantoro University. Data were collected through a five-point Likert scale questionnaire and analyzed using SEM-PLS with SmartPLS 4. The results show that functional and epistemic values have a significant effect on Brand Preference and Purchase Decision, while emotional and social values do not have a significant effect. Brand Preference was found to have a significant effect on Purchase Decision and mediated the effect of functional and epistemic values on Purchase Decision. These findings indicate that Gen Z considers rational and novelty aspects more than emotional and social status aspects when purchasing premium smartphones.